1998
DOI: 10.1152/ajprenal.1998.274.4.f791
|View full text |Cite
|
Sign up to set email alerts
|

Role of NO in cyclosporin nephrotoxicity: effects of chronic NO inhibition and NO synthases gene expression

Abstract: The role of nitric oxide (NO) during cyclosporin renal vasoconstriction was evaluated by glomerular hemodynamic and histological changes produced by chronic NO synthesis inhibition and neuronal (nNOS), inducible (iNOS), and endothelial (eNOS) NO synthases mRNA expression in renal cortex and medulla. Uninephrectomized rats treated during 7 days with vehicle (Veh), cyclosporin A (CsA) 30 mg/kg, CsA + nitro-l-arginine methyl ester (l-NAME), and Veh +l-NAME (10 mg/dl) in the drinking water were studied. Increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
47
0
3

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 22 publications
6
47
0
3
Order By: Relevance
“…Forstermann et al 1998), and a LPS-evoked NO-inhibition of eNOS by NO produced from iNOS has previously been demonstrated in the kidney (Schwartz et al 1997). The coupled changes in iNOS and eNOS expression are in correspondence with those found during endotoxemia and sepsis in different species including human (see Traber 1996), and are also in agreement with previous studies combining quantitative mRNA-expression and immunocytochemical localization of NOS-proteins, after LPS-treatment in rats and glomerulonephritis in humans (Liu et al 1996, Schwartz and Blantz 1999, Bobadilla et al 1998, Furusu et al 1998, Cattell 2002. In general, induction of iNOS and NO produced as part of an immunological response may cause acute renal failure and dysfunction of different organs (see Schwartz and Blantz 1999, Heyman 2000a, 2000b, Shieh et al 2000.…”
Section: Alterations In Nnos By MD Cells As Part Of Compensatory Intesupporting
confidence: 88%
See 1 more Smart Citation
“…Forstermann et al 1998), and a LPS-evoked NO-inhibition of eNOS by NO produced from iNOS has previously been demonstrated in the kidney (Schwartz et al 1997). The coupled changes in iNOS and eNOS expression are in correspondence with those found during endotoxemia and sepsis in different species including human (see Traber 1996), and are also in agreement with previous studies combining quantitative mRNA-expression and immunocytochemical localization of NOS-proteins, after LPS-treatment in rats and glomerulonephritis in humans (Liu et al 1996, Schwartz and Blantz 1999, Bobadilla et al 1998, Furusu et al 1998, Cattell 2002. In general, induction of iNOS and NO produced as part of an immunological response may cause acute renal failure and dysfunction of different organs (see Schwartz and Blantz 1999, Heyman 2000a, 2000b, Shieh et al 2000.…”
Section: Alterations In Nnos By MD Cells As Part Of Compensatory Intesupporting
confidence: 88%
“…The complex regulation of eNOS expression in the kidney is influenced by a large number of compounds and physiological conditions (see review by Kleinert et al 2003). An indirect influence on eNOS expression via altered iNOS expression has been indicated to affect glomerular function specifically (Cattell 2002, Zhou et al 2000, Bobadilla et al 1998. Thus, during endotoxemia the lowered eNOS expression in arterioles and glomeruli may be influenced by nearby produced NO, both from the iNOS cells in the Bowman's capsule and cortical tubules and from nNOS cells in MD.…”
Section: Alterations In Nnos By MD Cells As Part Of Compensatory Intementioning
confidence: 99%
“…A reduction of the ultrafiltration coefficient (K f ) has also been observed. The decrease in these two hemodynamic variables lead to a significant reduction of the single-nephron glomerular filtration rate and thus renal dysfunction (7,10,11). The precise mechanism by which CsA induced renal vasoconstriction has not been clearly established.…”
Section: Mechanisms Of Csa Nephrotoxicitymentioning
confidence: 99%
“…The precise mechanism by which CsA induced renal vasoconstriction has not been clearly established. Results from several studies indicate that vascular dysfunction induced by CsA results from an increase in vasoconstrictor factors that include endothelin (28), thromboxane (46), and angiotensin II (45,65) as well as a reduction of vasodilator factors such as prostacyclin (45) and nitric oxide (NO) (10,11,17,34,69). Thus an imbalance in the release of vasoactive substances seems to be responsible for renal vasoconstriction.…”
Section: Mechanisms Of Csa Nephrotoxicitymentioning
confidence: 99%
“…In a previous study, our group has shown that L-arginine-administration in slightly lower dosages could partly improve renal function after ischemia without CNI-treatment, whereas Lmonomethyl-arginine, another unspecific NOS-inhibitor, had no effect [22]. For calcineurin inhibitors, an influence on intrarenal NO-synthesis was reported as well: CsA supplied with the drinking-water increases endothelial NOS-expression in the renal cortex of Wistar rats, most likely as counterregulation of the release of endothelin and other vasoconstrictors [4]. The group of De Nicola observed in micropuncture studies that chronic CSA-treatment decreased single nephron GFR and plasma flow, due to disturbances in afferent arteriolar autoregulation, which was partially prevented by arginine-feeding [6].…”
mentioning
confidence: 99%